2014
DOI: 10.1038/nclimate2361
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated microbial turnover but constant growth efficiency with warming in soil

Abstract: Rising temperatures are expected to reduce global soil carbon (C) stocks, driving a positive feedback to climate change 1-3. However, the mechanisms underlying this prediction are not well understood, including how temperature affects microbial enzyme kinetics, growth efficiency (MGE), and turnover 4,5. Here, in a laboratory study, we show that microbial turnover accelerates with warming and, along with enzyme kinetics, determines the response of microbial respiration to temperature change. In contrast, MGE, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
199
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 287 publications
(223 citation statements)
references
References 38 publications
11
199
3
1
Order By: Relevance
“…Although microbial CUE of higher quality substrates is unresponsive to temperature (Frey et al, 2013), the pre-incubated litter contained more low-quality substrates (Table 1) and therefore should have lower CUE. Alternatively, recycling of microbial biomass results in high microbial CUE (Schimel and Weintraub, 2003;Manzoni et al, 2012), and increased microbial turnover has been observed with warming (Hagerty et al, 2014). The greater proportion of lipid-derived C in the preincubated litter (Table 1) was either derived from the selective enrichment of plant-derived lipids (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although microbial CUE of higher quality substrates is unresponsive to temperature (Frey et al, 2013), the pre-incubated litter contained more low-quality substrates (Table 1) and therefore should have lower CUE. Alternatively, recycling of microbial biomass results in high microbial CUE (Schimel and Weintraub, 2003;Manzoni et al, 2012), and increased microbial turnover has been observed with warming (Hagerty et al, 2014). The greater proportion of lipid-derived C in the preincubated litter (Table 1) was either derived from the selective enrichment of plant-derived lipids (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…3a); therefore the simulated equilibrium soil carbon by model B increases with warming if the warmed soil temperature is above 0 • C. Figure 3b shows that T x for model B decreases with an increase in b or x. When the turnover rate of microbial biomass is not sensitive to soil temperature (b = 0) and x = 0.016 • C −1 as the default value for model B, T x is about 35 • C. For b = 0.063, as estimated by Hagerty et al (2014), T x < 0 • C; therefore the equilibrium soil carbon pool size as simulated by model B always increases with soil warming for most terrestrial ecosystems, irrespective of the value of x.…”
Section: Response Of Soil Carbon To Warmingmentioning
confidence: 98%
“…For example, there has been debate about the temperature sensitivities of microbial biomass turnover rate and microbial growth efficiency (Frey et al, 2013;Hargety et al, 2014), and the simulated sensitivity of soil carbon to warming (Hagerty et al, 2014). Regardless of the temperature sensitivity of microbial growth efficiency, model A always simulates a decrease in the equilibrium soil carbon under warming, whereas model B can simulate an increase or a decrease in the equilibrium soil carbon under warming, depending on the temperature sensitivities of microbial growth efficiency and turnover rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations